First record and new species of the genus Calambus Thomson (Coleoptera, Elateridae, Dendrometrinae) from Taiwan - Arimoto, Kôichi (Zootaxa, 2020)
Calambus taiwanensis sp. n. is described from Taiwan, as the first record of the genus Calambus. This species is distinguished from its congeners by the male antennae extending beyond the apex of the pronotal hind angles by two apical antennomeres, antennomere III obconical and slightly longer than II, male aedeagus not expanded apically and without lateral subapical barbs, female genitalia with robust baculum and bursa copulatrix without sclerotized piece. The species is not included in any group suggested in past studies. A key to the five genera of the tribe Prosternini from Taiwan is provided.